Determinants of Green Banking Adoption: A Theoretical Framework - Asim Ali Bukhari, Syed; Hashim, Fathyah; Amran, Azlan (KnE Social Sciences, 2019)
All around the world, Green Banking has gained a tremendous moment in the last few decades. The green movement in the banking sector was triggered due to the escalating global climate change being caused by environmental degradation. Mostly attributed to the manufacturing sector, it has now been realized that banks are one of the major causes of the global climate change both directly and indirectly. This has caused an increased focus and stakeholder pressure for Green Banking adoption at the global level. Based on the Institutional theory, this study proposes a framework for examining the relationship between organizational adoption determinants and the adoption of Green Banking. The proposed framework is based on Institutional theory and justified through the existing literature. The study proposes the hypothesis for examining the relationship between determinants and Green Banking adoption. External or institutional factors are proposed to play an essential role in influencing a bank’s adoption of Green Banking practices. The proposed framework can be adopted by a country’s regulatory authorities and the individual banks in order to identify the factors that can positively influence and facilitate the adoption of Green Banking. Keywords:greenbanking,greenbankingadoption,stakeholderpressures,institutional theory, green banks.